Identifikasi Sarana dan Prasarana Sebagai Proses Pengembangan Wilayah Pesisir Barat Kota Tarakan - Eko Prihartanto (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
The availability of infrastructure is considered a top priority for the development of coastal areas. Completeness of infrastructure in an area will bring investment from outside into the area. The availability of infrastructure also has a backward relationship that is higher than the relationship in the future which means the availability of infrastructure is more able to encourage the growth of the upstream sector compared to the downstream sector so that infrastructure has an important role in the economic development of coastal areas such as Coastal Selumit Pantai. The method used is a Scalogram Analysis used to see an overview of the level of development of an area administratively using the completeness of facilities and infrastructure (infrastructure) in the region. questionnaire and interview to collect data, with resident respondents in Selumit Pantai village. The results obtained are categories that are included in the hierarchy of the availability of facilities and infrastructure such as There are three hierarchies in Selumit Pantai Village based on a scalogram analysis in which the RT (RT) reviewed is RT 17, 18, 19, 21, and 28 covering the hierarchy 3 with low development area.